Perbaikan Desain Produk Hand Juicer untuk Menurunkan Waktu dan Biaya Produksi dengan Metode DFMA - Desi Santi Riyana; Meutia Fadilla; Sastika Amalia (Jurnal Teknik Mesin Unsyiah, 2020)
Design for Manufacturing and Assembly (DFMA) is a method used by designers and engineers to design a product with a smaller number of components. The goal is to facilitate the manufacturing and assembly processes so as to reduce production time and costs. This article discusses the use of the DFMA method to redesign hand juicer product by changing the raw material from stainless steel to polypropylene plastic to make the product lighter, more practical and easier to clean. DFMA analysis on the redesign of hand juicer products shows a reduction in the number of product components from 6 components to 2 components. In addition, production time was reduced from 135 seconds to 120 seconds, while production costs were reduced from IDR166,000 to IDR56,200.